条件x=0,y=1的特解;n (dy)/(dx)=(1+y^2)/(xy+x^3y)(4)(1+x)ydx+(1-y)xdy=0;(5)(y+x)dy+(x-y)dx=0;(6)x(dy)/(dx)-y+√(x^2-y^2)=0 ;(7)tanydx-cotxdy=0 ;(8) (dy)/(dx)+(e^(x^2+y))/y=0 :(9) x(lnx-lny)dy-ydx=0 ;(10)(dy)/(dx)=e...
初值条件x=0,y=1的特解③ (dy)/(dx)=(1+y^2)/(xy+x^3y)(4)(1+x)ydx+(1-y)xdy=0:(5)(y+x)dy+(x-y)dx=0(6) x(dy)/(dx)-y+√(x^2-y^2)=0=0(7) tanydx-cotxdy=0 ;(8) (dy)/(dx)+(e^(x^2+y))/y=0(9) x(lnx-lny)dy-ydx=0 :(10) (dy)/(dx)=...
y(2xy+e^(x))^(x)dx-e^(x)dy=0 (e ^ (y) +1) cos xdx + e ^ (y) sin xdy = 0 The solution ofy(2xy+ex)dx−exdy=0is (A)x2+ye−x=C(B)xy2+e−x=C(C)xy+e−xx2=C(D)x2+exy=C View Solution The solution of ex(y2−1)y{xy2dy+y3dx}+{ydx−xdy}=0...
D(XY) = E{[XY-E(XY)]^2} = E{X²Y²-2XYE(XY)+E²(XY)} = E(X²)E(Y²)-2E²(X)E²(Y)+E²(X)E²(Y)= E(X²)E(Y²)-E²(X)E²(Y)如果 E(X) = E(Y) = 0,那么 D(XY) = E(...
Answer to: Solve the following ordinary differenrial equations: Both are non exact differential equations. a. y^2 dx + xy dy = 0 b. y' = 2xy - x...
xy'-ylny=0 ;(e^y)/(1+e^y)d=(2x)/(1+x^2)dx ;3. 1/(y+3)dy=2xdx ;4. y'=(1+y^2)/(xy+x^2y);xy+x3y5. (1+x)ydx+(1-y)xdy=0;6. y'=e^(x-y) ;7. x(y^2-1)dx+y(x^2-1)dy=0 ;8. y'=(1+x^2)(1+y^2) ;9. y'=2xy,y|_(x=...
(3) 3xy^2dy=(2y^3-x^3)dx ((4) y'=y/x+siny/x(5) xy'=y+√(x^2+y^2),x0(6) (xe^(y/x)+y)dx=xdy , y(1)=0(7) (y^2-3x^2)dy=2xydx , y(0)=1(8) (x^2+y^2)dx=xydy , y(1)=0(9) xy^2dy=(x^3+y^3)dx ,y(1)=0(10 y'=(y/x)^...
Question: What is a solution to the differential equation dy/dx - y - e^(3x) = 0? Differential Equation: A differential equation that is not separable can be solved by finding its integrating factor. If a differential equation is in the formdydx+P(x)y=Q(x)then its integrat...
∵d(2xy)=2xyln2•d(xy)=2xyln2•(ydx+xdy)d(x+y)=dx+dy∴2xyln2•(ydx+xdy)=dx+dy又x=0时,y=1∴代入上式得:dy|x=0=(ln2-1)dx 此题考查隐函数的微分,可以选择使用微分形式的不变性. 本题考点:复合函数微分法则;隐函数的求导法则. 考点点评:如果对微分形式的不变性不熟悉,此题也可以...
显然y=0,是方程的解。y≠0时,考虑到xdy^(-2)=(-2xdx)/y^(-3),因此方程两边乘以y^(-4),得 y^(-2)dx+xdy^(-2)-3y^(-4)dy=d[xy^(-2)]+dy^(-3)=0,因此xy^(-2)+y^(-3)=C。这个